THE EFFECT OF SYNCHRONOUS AND ASYNCHRONOUS EFL CLASS ON STUDENTS’ ACHIEVEMENT AT ELEVENTH GRADE OF SMAN TERPADU UNGGULAN 1 TANA TIDUNG - Manuk, Maria Carla; Ulfaika, Romlah; Fitriawati, Fitriawati (Universitas Borneo Tarakan, 2022)
The purpose of this study was to find out if synchronous and asynchronous could improve the student’s English achievement in the eleventh grade of SMAN Terpadu Unggulan 1 Tana Tidung. This research used a quasi- experimental research method to find out the differences before and after being taught using the approach. The subject of this study were the students of class XI at MIPA 1 and MIPA 3 with the total number of 52 students of SMAN Terpadu Unggulan 1 Tana Tidung in academic year of 2021/2022. The instrument was an essay of writing a paragraph. The result of this study indicated that there was no significant differences between the pretest and posttest both in synchronous and asynchronous class and it was proven by the result of students’ average score. The average score of the pretest in synchronous class was 62.68 and the average score of posttest was 62.86. The average score of pretest in asynchronous class was 61.67 and the average score of posttest was 63.96. The average score in posttest was relatively similar with the pretest score. It showed that there was no significant difference in student English achievement on pretest and posttest. The test result from the independent sample test showed that t-test (0.458) was lower than the t- table (1.676). Therefore, it can be concluded that synchronous and asynchronous was less effective in impoving the student English achievement at eleventh grade of SMAN Terpadu Unggulan 1 Tana Tidung.